Physico-chemical and Sensory Evaluation of Market Yoghurt in Nigeria - Olugbuyiro, Joseph A.O.; Oseh, Joy E. (Pakistan Journal of Nutrition, 2011)
This study examined the quality of some yoghurts made and sold in the Nigerian market. Nine commercially available brands of yoghurt drinks which represent seven different manufacturers were randomly selected. The samples included seven plain yoghurt and two fruit yoghurt samples. All yoghurt samples were analyzed for chemical properties (moisture%, ash %, total solids, SNF, fat, pH and titratable acidity) and the organoleptic tests (color, thickness, appearance, body, texture, taste, smell, flavor and over all acceptability). The results of the study showed that the physico-chemical composition of the manufactured yogurts was different. The pH values of the samples ranged between 3.70-4.33 which were reasonably suitable for yoghurt marketed in tropical areas. No direct relationship was observed between pH values and titratable acidity. There was marked variation in the % fat content of the products. The results of the sensory evaluation revealed that flavor with respect to taste and smell had significant influence (p